Essentiality of custom ('urf/'adat) in issuing fatwa (Ifta'): a special reference to Ibn Abidin's Sharh Uqud Rasm al-Mufti - Ali, Mohammed Farid (Institut Pengurusan dan Penyelidikan Fatwa Sedunia (INFAD), Universiti Sains Islam Malaysia (USIM), 2016)
Muftis not always are aware of their people’s custom (‘urf/adat) and this at times result their fatwa not to be at par with the challenges of the developing societies. This paper emphasizes the importance of custom in shari‘ah, essentiality of its knowing for the jurists/muftis, and its essentiality in the works of fatwa giving (al-ifta’), referring to as Ibn Abidin cited in his Sharh ‘Uqud Rasm al-Mufti. The paper concludes that there is no way out for a mufti to issue a fatwa, while not facing custom of his time. Fatwa is a tool for the evolution of shari‘ah in dealing with the evolving worldly affairs, and guarantees the most suitable solution in changing circumstances, if custom of the people are kept in consideration.